Burn your fat—a unique DIY board game about triacylglycerol breakdown - Milonaitytė, Dovilė; Kuda, Ondrej (Frontiers in Education, 2024)
Understanding metabolic pathways is challenging for students due to their complex nature and intricate interdependencies. To address this problem, gamification has emerged as a promising approach to make scientific concepts accessible and engaging. We present a DIY educational activity focusing on lipid and glucose metabolism to clarify the basic principles of biochemical transformations and provide practical educational resources for lecturers. The activity is designed to be accessible and requires minimal resources, using physical media such as printed boards and dice. It consists of two parts: an introductory session where students build a triacylglycerol molecule and a board game where teams compete to metabolically break down triacylglycerols and obtain ATP. The process in governed by rules based on metabolic transformations, with players taking on roles as walkers, counters, transformers, and strategists to encourage cooperation. The game aligns with the theories of cognitivism and constructivism and emphasizes knowledge acquisition, the formation of mental structures, and active learning through experience. It promotes a socio-cultural perspective and the development of interpersonal skills by encouraging teamwork, cooperation, and problem-solving. The thematic focus on obesity provides real-world context, and the DIY concept, 3D printing capability, and potential for creating extensions encourage student engagement and customization. The activity effectively teaches metabolic networks to high school students, is helpful for graduate students in visualizing experimental problems, increased engagement in the classroom and interest in the life sciences. A simplified version has also been used for the general public at science fairs, highlighting its versatility and accessibility.